THE INFLUENCE OF ISLAMIC FINANCIAL LITERACY AND RISK AWARENESS ON MSMEs' DECISIONS IN CHOOSING ISLAMIC BANKING FINANCING IN KUALUH LEDONG DISTRICT - Nuraini Nuraini; Zuhrinal M. Nawawi; Juliana Nasution (Postgraduate Bosowa University Publishing, 2026)
The growth of Islamic banking in Indonesia has continued to show a positive trend, particularly in financing distribution and asset expansion. However, the utilization of Islamic banking financing by Micro, Small, and Medium Enterprises (MSMEs) remains relatively limited despite the sector’s substantial contribution to national economic development. This condition indicates that financing decisions are influenced not only by the availability of financial services but also by behavioral and cognitive factors. This study aims to examine the influence of Islamic financial literacy and risk awareness on MSMEs’ decisions in choosing Islamic banking financing in Kualuh Ledong District. The study employed a quantitative approach using an associative research design. Primary data were collected through questionnaires administered to 50 MSME owners selected using purposive sampling techniques. Data were analyzed using multiple linear regression, supported by validity and reliability tests, classical assumption tests, coefficient of determination analysis, and hypothesis testing through t-tests and F-tests. The findings reveal that Islamic financial literacy has a positive but insignificant effect on MSMEs’ decisions in selecting Islamic banking financing. In contrast, risk awareness has a positive and statistically significant effect on financing decisions. Simultaneously, Islamic financial literacy and risk awareness significantly influence MSMEs’ financing decisions, with a coefficient of determination of 68.1%, indicating that both variables explain a substantial proportion of decision-making behavior. The results suggest that risk considerations play a more dominant role than financial literacy in shaping financing choices among MSMEs. This study contributes to the Islamic finance literature by demonstrating that financing decisions are better explained through the integration of cognitive and risk-perception factors. The findings also provide practical implications for Islamic banking institutions to strengthen risk-management education alongside efforts to improve Islamic financial literacy among MSME actors.